Intrahospital survival and neurological recovery after out of hospital cardiac arrest - Jaraković, Milana; Aleksić, Vesna; Bjelica, Snežana; Dimić, Sonja; Kovačević, Mila; Petrović, Milovan; Keča, Stevan; Maletin, Srđan; Ivanišević, Dragan (Halo 194 Scientific Journal of Emergency Medicine, 2022)
Introduction. Despite advances in therapeutical approach, survival and neurological recovery after out-of-hospital cardiac arrest still remain poor.Aim. The aim of the study was to evaluate predictors of intrahospital survival and neurological outcome among patients after out-of-hospital cardiac arrest and to evaluate influence of introduction of mild therapeutic hypothermia on intrahospital survival and neurological outcome among comatose patients after out-of-hospital cardiac arrest.Methods. The research was conducted as a retrospective observational analysis of the sample of patients hospitalized at the Cardiac Intensive Care Unit of the Institute of Cardiovascular Diseases of Vojvodina from January 2007 until November 2019 due to out-of-hospital cardiac arrest. Statistical analysis was performed using SPSS 17 statistical package.Results. The research included 506 survivors of OHCA. Multivariate regression analysis showed that: initial shockable rhythm (OR 3.301[2.002 - 5.441], p < 0.0005), duration of cardiopulmonary resuscitation ≤20 min (OR 5.144 [3.090 - 8.565], p < 0.0005) and Glasgow Coma Score >8 at admission (OR 0.152 [0.088 - 0.260], p < 0.0005) were predictors of intrahospital survival and good neurological outcome. Introduction of mild therapeutic hypothermia improved intrahospital survival (54.1% vs. 24.4%; p
Keywords: Out-of-hospital cardiac arrest; predictors of intrahospital survival; predictors of good neurological outcome; cardiopulmonary resuscitation; Glasgow Coma Score; shockable rhythm; mild therapeutic hypothermia